The Transcription Factor ArcA Modulates Salmonella’s Metabolism in Response to Neutrophil Hypochlorous Acid-Mediated Stress - Pardo-Esté, Coral; Castro-Severyn, Juan; Krüger, Gabriel I.; Cabezas, Carolina Elizabeth; Briones, Alan Cristóbal; Aguirre, Camila; Morales, Naiyulin; Baquedano, Maria Soledad; Sulbaran, Yoelvis Noe; Hidalgo, Alejandro A.; Meneses, Claudio; Poblete-Castro, Ignacio; et al. (Frontiers in Microbiology, 2019)
Salmonella Typhimurium, a bacterial pathogen with high metabolic plasticity, can adapt to different environmental conditions; these traits enhance virulence by enabling bacterial survival. Neutrophils play important roles in the innate immune response including production of microbicidal reactive oxygen species (ROS). In addition, the myeloperoxidase in neutrophils catalyzes the formation of hypochlorous acid (HOCl), a highly toxic molecule that reacts with essential biomolecules causing oxidative damage including lipid peroxidation and protein carbonylation. The bacterial response regulator ArcA regulates adaptive responses to oxygen levels and influences the survival of Salmonella inside phagocytic cells. Here, we demonstrate by whole transcriptomic analyses that ArcA regulates genes related to various metabolic pathways enabling bacterial survival during HOCl-stress in vitro. Also, inside neutrophils ArcA controls the transcription of several metabolic pathways by downregulating the expression of genes related to fatty acid degradation, lysine degradation, as well as arginine, proline, pyruvate and propanoate metabolism. ArcA also upregulates genes encoding components of the oxidative pathway. These results underscore the importance of ArcA in ATP generation inside the neutrophil's phagosome and its participation in bacterial metabolic adaptations during HOCl stress.